2017
DOI: 10.1002/alr.22041
|View full text |Cite
|
Sign up to set email alerts
|

Lack of additional effects of long‐term, low‐dose clarithromycin combined treatment compared with topical steroids alone for chronic rhinosinusitis in China: a randomized, controlled trial

Abstract: The combination of CLM + BUD for the treatment of first-time-diagnosed CRS in this Chinese population cohort did not show a better effect compared with a single BUD regimen, but it may have a better effect in some patients with increased IL-6 or IL-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 21 publications
0
33
1
Order By: Relevance
“…The reasons for exclusion are listed in Figure . Finally, 10 studies were included for qualitative synthesis and nine studies for quantitative synthesis . Characteristics of the included studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for exclusion are listed in Figure . Finally, 10 studies were included for qualitative synthesis and nine studies for quantitative synthesis . Characteristics of the included studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Ten trials studied 608 participants, 50.3% were male, with the mean age of 43.9 years (nine studies). All patients were adults with CRS: CRSsNP (three trials), CRSwNP (three trials), and mixed subtypes of CRS (a major population of CRSwNP [three trials] and CRSsNP [one trial]). Two trials measured the serum IgE level at enrollment .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons of these differences in findings might be different pheno-and endotype of disease. In his first trial Wallwork has already highlighted potential differences in phenotype that might predict the effect of macrolides, with patients with low IgE having a better outcome, and recently a number of uncontrolled evaluations point to a potentially larger effect of long-term antibiotics in patients with non-Th2 forms of the disease (4,5) . The study in this Journal pointing at a shift towards eosinophilic inflammation, and away from non-Th2 forms of CRS in Asia in the last decade, may explain why, especially in Asia, macrolide therapy has been very successful in the past, although it could currently be expected to be less effective in that region (6) .…”
Section: Long-term Antibiotics For Chronic Rhinosinusitis: Changing Vmentioning
confidence: 99%
“…Current guidelines suggest that macrolide use in CRS without nasal polyps (CRSsNP) and CRS with nasal polyps (CRSwNP) is optional. Deng et al . performed a randomized controlled trial of patients with CRS—both with and without polyps—to assess their responses to clarithromycin.…”
mentioning
confidence: 99%